2013
DOI: 10.1097/wnr.0b013e328364b948
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vertebrobasilar artery changes in patients with benign paroxysmal positional vertigo

Abstract: The aim of this study was to investigate vertebrobasilar artery (VBA) lesions in elderly patients with benign paroxysmal positional vertigo (BPPV) by magnetic resonance angiography. VBA lesions in patients older than 65 years of age with BPPV were prospectively investigated by magnetic resonance angiography. Vascular risk factors, blood vessel changes, and vertigo severity were recorded. Age-matched individuals without BPPV were included in the control group. Of 126 patients screened for this study, 104 were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…In patients with an intima–media thickness greater than 1.1 mm, the level of residual senses of positional vertigo was higher (Wada et al, 2009). A study by Zhang et al (2013) also revealed increased abnormalities in the vertebrobasilar arteries of BPPV patients. The severity of vertigo was correlated with vertebral artery stenosis, occlusion, or tortuosity (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In patients with an intima–media thickness greater than 1.1 mm, the level of residual senses of positional vertigo was higher (Wada et al, 2009). A study by Zhang et al (2013) also revealed increased abnormalities in the vertebrobasilar arteries of BPPV patients. The severity of vertigo was correlated with vertebral artery stenosis, occlusion, or tortuosity (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…A study by Zhang et al (2013) also revealed increased abnormalities in the vertebrobasilar arteries of BPPV patients. The severity of vertigo was correlated with vertebral artery stenosis, occlusion, or tortuosity (Zhang et al, 2013). These reports are in accordance with our findings (Table 1), which showed that patients with BPPV had a higher prevalence of hypertension and coronary artery disease.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies have investigated associations between vascular risk factors and BPPV, such as hypertension, DM, and hyperlipidemia, but the results were controversial (4,19). In addition, vascular comorbidities may also be risk factors for BPPV recurrence (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying causes of BPPV remain unclear. In recent decades, many studies have investigated risk factors for the occurrence of BPPV, including female gender, serum vitamin D deficiency, osteoporosis, vascular risk factors, head trauma, and other potential risk factors (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, there are some controversies among these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Besides microvascular damage, macrovascular damage is seen in people with diabetes and hypertension. Arteriosclerotic changes were seen in the carotid arteries of 71% of people with BPPV compared to 43% of people with other vestibular disorders [34], while stenosis or occlusion of the vertebrobasilar artery was seen in 21% of people with BPPV, compared to 6.8% of people without BPPV [42]. Elderly people (mean age 57.36±15.44 years) with BPPV and comorbidities like hypertension and diabetes have a higher risk of ischemic stroke (4.5% compared to 2.9% without BPPV) [17].…”
Section: Discussionmentioning
confidence: 99%